Importance of Physical Education in School - Abidova Sitora Khurramovna (International Journal of Scientific Trends, 2025)
Physical education is combined with intellectual, moral, work and aesthetic education. We need to use ped technologies in new ways to interest and increase the interest of the young generation in physical education from the school age. In order to fundamentally improve the teaching of physical education in general secondary schools and ensure the effectiveness of the system of continuous professional development of physical education teachers, to establish a regular improvement of their professional and physical skills.